Macroeconomic regimes, polices, and outcomes in the world - Schmidt-Hebbel, Klaus (Estudios de Economía, 2016)
This paper summarizes a research project focused on the empirical determinants of and interrelations between macroeconomic regimes, policies, and performance in the world. The project's hypotheses are structured into three related themes. The first aim is analyzing the determinants of the likelihood of adoption of macroeconomic policy regimes. The second project theme focuses on cyclicality of macroeconomic policies and accuracy in attaining inflation targets. Finally, the project tests for the behavior of two key macroeconomic variables -economic growth and inflation- focusing on their sensitivity to different macroeconomic regimes and policies. A large world database was assembled for this project from both publicly available and private databases. Data coverage extends to more than 100 countries, with annual time series extending from 1970 to 2008. A wide spectrum of frontier estimation techniques is applied to the country panel data series, appropriate for discrete-choice and continuous variable estimation. The key research results are the following. Country choice of macroeconomic policy regimes (exchange-rate regimes, money-based targeting, inflation targeting, and rule-based fiscal regimes) is explained by countries’ structural and institutional features, macroeconomic performance, financial development, and international integration. The cyclical behavior of fiscal policy reflects the quality of country institutions, financial openness, and financial development. Central bank accuracy in meeting inflation targets is also a result of domestic institutional strength and macroeconomic credibility. Long-term growth is significantly shaped by the quality of policies, financial development, foreign aid, and exchange-rate misalignment, in addition to standard growth determinants. Growth volatility is a result of domestic macroeconomic policy volatility, external shocks, international integration, and financial development. Country inflation rates are determined by international factors and domestic determinants, including fiscal policy, institutional development, monetary and exchange-rate regimes, and financial depth and integration.